Aviation Safety Management System Arrangements to Realize Security and Safety at Halim Perdana Kusuma Airport - Dwi Retno Astuty; Niru Anita Sinaga; Mardianis Mardianis (JURNAL HUKUM SEHASEN, 2023)
Regulation of aviation safety management system to realize security and safety at Halim Perdana Kusuma Airport. This thesis raises the issue of aviation safety arrangements based on international rules at the airport in relation to the application of safety management systems and the implementation of these rules in accordance with Law Number 1 of 2009 concerning Aviation and its implementing regulations, especially at Halim Perdana Kusuma Airport. The safety and security of national aviation regulated in the Aviation Law includes guidelines that are in accordance with ICAO provisions regarding the State Safety Program. ICAO standards require Indonesia as a member state to develop a National Aviation Safety and Security Program to achieve an Acceptable Level of Safety (AIoS) and a safety management system for aviation service providers. Furthermore, researchers conduct legal analysis of primary legal materials and secondary legal materials related to the problems studied. The type of research that the author uses is an empirical juridical research method conducted by means of field research through interviews and examining library materials or secondary data. In the discussion of this research, it is known that aviation safety arrangements based on international rules at the airport in relation to the application of the Safety Management System are regulated based on the provisions of ICAO Annex 14 which has introduced the application of the Safety Management System in the operation of the Airport, and the provisions of ICAO Annex 19 concerning Safety Management, the framework of the Safety Management System in its implementation is in accordance with Law Number 1 of 2009 concerning Aviation as a guideline in implementing aviation security and safety arrangements at Halim Perdana Kusuma Airport.